A LITERATURE REVIEW ON ORAL HYPOGLYCEMIC DRUGS – MECHANISTIC ASPECTS - SYED WAJID; MENAKA M; FAZIL AHMED; SANA SAMREEN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Diabetes mellitus (DM) is a worldwide rising concern that leads to an increased rate of morbidity, mortality, and health-care costs. DM is a chronic, endocrine disorder associated with hyperglycemia. The current estimated DM prevalence is over 422 million and has been progressively increasing over the past decades. Consequently, it is considered a significant problem in health-care settings. Health-care professionals who deal with such patients need to have an adequate information and drug therapy management including drugs and its regimen that are presently available in the market. This review provides an overview of potential diabetic drugs and their mechanisms. Hence, it will be proved beneficial for health-care professionals.